Temporal and spatial variation of grey water (sullage) properties from commercial and residential catchments - Asadsangabifard, Mohammadjavad; Ismail, Zubaidah; Yusop, Zulkifli; Ong, Zhi Chao; Mohd, Nuruol Syuhadaa; Roushenas, Peiman; Tam, Jun Hui (Desalination Publications, 2018)
Water pollution has been one of the major concerns in Malaysia and its increasing severity impacts negatively on the sustainability of water resources. It limits the total water availability dramatically due to the exorbitant cost for treating polluted waters and in some cases, polluted waters are not treatable for consumption. Grey water (sullage) is one of the important sources of pollution, which is released from residential and commercial premises into the rivers without prior treatment. Before initiating measures into developing or implementing grey water reuse and treatment systems, it is more appropriate to conduct a detailed study on the discharged grey water quality and characteristics. The present research studies the chemical, biological and physical characteristics of grey water released from residential and commercial premises near the Melana River, which is located at Skudai, Johor, Malaysia. The variations in parameters, namely, BOD, COD, pH and turbidity, with respect to different days and times (temporal) as well as different sampling sites (spatial) are investigated. The results reveal that grey water quality and characteristics are almost similar to those taken from literature and suggest that the treatment of grey water is necessary for intended reuse purposes.